2012
DOI: 10.1586/epr.11.80
|View full text |Cite
|
Sign up to set email alerts
|

The scientific exploration of saliva in the post-proteomic era: from database back to basic function

Abstract: The proteome of human saliva can be considered as being essentially completed. Diagnostic markers for a number of diseases have been identified among salivary proteins and peptides, taking advantage of saliva as an easy-to-obtain biological fluid. Yet, the majority of disease markers identified so far are serum components and not intrinsic proteins produced by the salivary glands. Furthermore, despite the fact that saliva is essential for protecting the oral integuments and dentition, little progress has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 118 publications
5
71
0
Order By: Relevance
“…aliva plays a key role in host defense against invading pathogens (1)(2)(3)(4). Among the more than 2,000 proteins and peptides found in saliva (5), many exhibit direct antimicrobial activity (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…aliva plays a key role in host defense against invading pathogens (1)(2)(3)(4). Among the more than 2,000 proteins and peptides found in saliva (5), many exhibit direct antimicrobial activity (6).…”
mentioning
confidence: 99%
“…Thus, binding of salivary proteins to pathogens is thought to play an important role in preventing systemic infections. In hospitalized patients, the protective and antimicrobial functions of saliva, which play a crucial role in host defense against invading pathogens (1)(2)(3), are frequently impaired by reduction of salivary flow or lack of salivary secretion (9)(10)(11). Under such conditions of dry mouth and poor oral hygiene, the normal commensal oral microflora shifts to a community that harbors a higher number of pathogens (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For a given quantity of quinine, subjects with lower levels of histatin 5 had therefore more free quinine which could interact with their taste receptors, thereby increasing their sensitivity. Another example of salivary protein -tastant interaction has been suggested by [31] based on the demonstration by 1 H-NMR that the PROP molecule could interact with the arginine and lysine amino-acids. This investigation followed a study where top-down analysis of saliva of supertasters vs nontasters of PROP revealed that saliva of supertasters had higher levels of basic proline-rich proteins (PRPs), in particular the Ps1 protein which contains a high proportion of arginine and lysine [9].…”
Section: Taste Sensitivitymentioning
confidence: 99%
“…Whole saliva contains a wide variety of proteins and peptides, of glandular or blood origin, with diverse functions, namely proteins that participate in teeth and oral tissues protection, as well as proteins related to ingestive and digestive processes [1]. Several studies, in animals and humans, present evidences that saliva is involved in eating behaviour [e.g.…”
Section: Introductionmentioning
confidence: 99%